2017
DOI: 10.1093/aje/kwx207
|View full text |Cite|
|
Sign up to set email alerts
|

Examination of Cause-of-Death Data Quality Among New York City Deaths Due to Cancer, Pneumonia, or Diabetes From 2010 to 2014

Abstract: The cause-of-death (COD) statement on the standard US death certificate is a valuable tool for public health practice, but its utility is impaired by reporting inaccuracies. To assess the quality of CODs reported in New York City, we developed and applied a quality measure to 3 leading CODs: cancer, pneumonia, and diabetes. The COD quality measure characterized 5 common issues with COD completion: nonspecific conditions as the underlying COD (UCOD); UCOD discrepancies; the presence of only 1 informative cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
1
19
0
3
Order By: Relevance
“…While this study is not generalizable to all of NYC, it does suggest that hospital-level investigation can be helpful in examining entrenched systematic bias surrounding death certificate completion. Another study of the quality of cause of death reporting in NYC showed that >60% of death certificates listing pneumonia as the underlying cause of death were of limited quality [27]. When completing death certificates, physicians use their best judgment and the medical information available at the time of death to work back from the immediate cause of death to the underlying cause of death [28].…”
Section: Discussionmentioning
confidence: 99%
“…While this study is not generalizable to all of NYC, it does suggest that hospital-level investigation can be helpful in examining entrenched systematic bias surrounding death certificate completion. Another study of the quality of cause of death reporting in NYC showed that >60% of death certificates listing pneumonia as the underlying cause of death were of limited quality [27]. When completing death certificates, physicians use their best judgment and the medical information available at the time of death to work back from the immediate cause of death to the underlying cause of death [28].…”
Section: Discussionmentioning
confidence: 99%
“…Selain penyakit menular, perhatian pemerintah saat ini adalah meningkatnya kematian dikarenakan penyakit yang tidak menular sehingga para pembuat kebijakan, pakar epidemiologi dan para pengambil keputusan harus fokus pada permasalah ini (Satman et al, 2013) (Walker, 2012) Sebanyak 120 surat kematian yang dilaporkan, untuk ketepatan penetuan UCOD masih ada dibawah 50% hal ini dibuktikan ketika peneliti menganalisis meggunakan tabel MMDS. Ketepatan dalam menentukan UCOD tidak hanya berdampak terhadap pelaporan kematian (Redelings, Wise and Sorvillo, 2007) (Falci et al, 2018), namun dalam penentuan tarif layanan kesehatan yang diberikan serta ketepatan pengambilan keputusan untuk pemangku kebijakan (Hazard et al, 2018) (Morano and Watkins, 2017). Pada laporan kematian diatas dikategorikan berdasarkan penggolongan diagnosis, dari hasil analisis diagnosis penyebab kematian adalah penyakit tidak menular, sehingga diperlukan perhatian khusus tidak hanya pemberi layanan kesehatan tetapi juga pada pengambil keputusan atau kebiajakan kesehatan (Mellhammar et al, 2016) (Tobergte and Curtis, 2013).…”
Section: Kualitas Ucodunclassified
“…9 A study in 2017 examining the quality of COD reporting found that death certificates for pneumonia-related deaths were more likely than death certificates for cancer and diabetes to be incomplete or have other quality-related issues. 10 The reasons for this discrepancy are unclear but may be related to uncertainties inherent to pneumonia diagnosis, 11 particularly in patients with multiple concurrent medical problems. Furthermore, limited data exist on how logistical factors (such as a relative unfamiliarity with a patient after a change in physician schedule) may contribute to misreporting on death certificates.…”
mentioning
confidence: 99%